2020
DOI: 10.1155/2020/4301891
|View full text |Cite
|
Sign up to set email alerts
|

Active Compound Identification in Extracts of N. lappaceum Peel and Evaluation of Antioxidant Capacity

Abstract: Nephelium lappaceum and its by-products have great potential in the agricultural, pharmaceutical, and food industries. Some studies have shown that N. lappaceum by-products exhibit antimicrobial, antioxidant, antidiabetic, and anticancer properties. However, studies focused on identifying these compounds are rare. The availability of polyphenolic compounds can vary according to environmental conditions, soil, plant variety, and agronomic management. Therefore, in this study, the active compounds in extracts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 79 publications
0
22
1
Order By: Relevance
“…Clearly, 60% ethanol was a more proper solvent than pure water and ethanol. Other authors found that the hydroethanolic (60%) solvent provided higher yield of flavonoids than aqueous and ethanolic solvent in rambutan peel extraction using ultrasound and boiling [ 19 ]. The xanthones ( Figure 3 a) founded in mangosteen peel were mangostin, garcinone-E, gartanin and smeathxanthone-A, whereas mango peel contains mangiferin and quercetin ( Figure 3 b) derivatives as major flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, 60% ethanol was a more proper solvent than pure water and ethanol. Other authors found that the hydroethanolic (60%) solvent provided higher yield of flavonoids than aqueous and ethanolic solvent in rambutan peel extraction using ultrasound and boiling [ 19 ]. The xanthones ( Figure 3 a) founded in mangosteen peel were mangostin, garcinone-E, gartanin and smeathxanthone-A, whereas mango peel contains mangiferin and quercetin ( Figure 3 b) derivatives as major flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…The oral toxicity of geraniin-and geraniin-enriched extracts revealed that the LD 50 cut off value of geraniin-and geraniin-enriched extracts (2000 mg/kg body weight) had no significant adverse effects to rat's body weight, water intake, histopathological, haematological and biochemical metabolites. However, a study found that rats experienced diarrhoea and the histopathology stain of the hepatocyte was observed to be 'foamy' [26]. Hence, caution should be taken while exploring the therapeutic effect of geraniin in N. lappaceum because of its potential to cause liver abnormalities.…”
Section: Chemical Profile Of N Lappaceum 21 Peelmentioning
confidence: 99%
“…However, another study indicated that the use of ethyl acetate contributes to high antioxidant activities [48]. This is due to the difference in solubility of active compounds in solvents with different polarities [26].…”
Section: Antioxidant Activities Of N Lappaceummentioning
confidence: 99%
“… 33 Studies have shown that extracts from rambutan peel possess ellagitannins that exhibit various biological activities in humans. 31 , 34 Among the ellagitannins, geraniin is the major compound in rambutan peel. 27 Geraniin is a substance that possesses a broad range of biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there has been an increasing global demand for bioactive compounds from plants by the pharmaceutical, cosmetic, and nutraceutical industries, as a result of their presumed roles in disease prevention, nutritional value, and ability to address human skin-related issues . Studies have shown that extracts from rambutan peel possess ellagitannins that exhibit various biological activities in humans. , Among the ellagitannins, geraniin is the major compound in rambutan peel . Geraniin is a substance that possesses a broad range of biological activities.…”
Section: Introductionmentioning
confidence: 99%